Effect of Solvent and Protonation/Deprotonation on Electrochemistry, Spectroelectrochemistry and Electron‐Transfer Mechanisms of N‐Confused Tetraarylporphyrins in Nonaqueous Media. Issue 6 (17th December 2014) - Xue, Songlin; Ou, Zhongping; Ye, Lina; Lu, Guifen; Fang, Yuanyuan; Jiang, Xiaoqin; Kadish, Karl M.
Abstract A series of N‐confused free‐base meso‐substituted tetraarylporphyrins was investigated by electrochemistry and spectroelectrochemistry in nonaqueous media containing 0.1 M tetra‐n‐butylammonium perchlorate (TBAP) and added acid or base. The investigated compounds are represented as (XPh)4NcpH2, in which "Ncp" is the N‐confused porphyrin macrocycle and X is a OCH3, CH3, H, or Cl substituent on the para position of each meso‐phenyl ring of the macrocycle. Two distinct types of UV/Vis spectra are initially observed depending upon solvent, one corresponding to an inner‐2H form and the other to an inner‐3H form of the porphyrin. Both forms have an inverted pyrrole with a carbon inside the cavity and a nitrogen on the periphery of the π‐system. Each porphyrin undergoes multiple irreversible reductions and oxidations. The first one‐electron addition and first one‐electron abstraction are located on the porphyrin π‐ring system to give π‐anion and π‐cation radicals with a potential separation of 1.52 to 1.65 V between the two processes, but both electrogenerated products are unstable and undergo a rapid chemical reaction to give new electroactive species, which were characterized in the present study. The effect of the solvent and protonation/deprotonation reactions on the UV/Vis spectra, redox potentials and reduction/oxidation mechanisms is discussed with comparisons made to data and mechanisms for the structurally related free‐base corroles and porphyrins.